Arsenite response in Coccomyxa sp. Carn explored by transcriptomic and non‐targeted metabolomic approaches. (15th February 2016) - Koechler, Sandrine; Bertin, Philippe N.; Plewniak, Frédéric; Baltenweck, Raymonde; Casiot, Corinne; Heipieper, Hermann J.; Bouchez, Olivier; Arsène‐Ploetze, Florence; Hugueney, Philippe; Halter, David
Summary: Arsenic is a toxic metalloid known to generate an important oxidative stress in cells. In the present study, we focused our attention on an alga related to the genus C occomyxa, exhibiting an extraordinary capacity to resist high concentrations of arsenite and arsenate. The integrated analysis of high‐throughput transcriptomic data and non‐targeted metabolomic approaches highlighted multiple levels of protection against arsenite. Indeed, C occomyxa sp. Carn induced a set of transporters potentially preventing the accumulation of this metalloid in the cells and presented a distinct arsenic metabolism in comparison to another species more sensitive to that compound, i.e. E uglena gracilis, especially in regard to arsenic methylation. Interestingly, C occomyxa sp. Carn was characterized by a remarkable accumulation of the strong antioxidant glutathione (GSH). Such observation could explain the apparent low oxidative stress in the intracellular compartment, as suggested by the transcriptomic analysis. In particular, the high amount of GSH in the cell could play an important role for the tolerance to arsenate, as suggested by its partial oxidation into oxidized glutathione in presence of this metalloid. Our results therefore reveal that this alga has acquired multiple and original defence mechanisms allowing the colonization of extreme ecosystems such as acid mine drainages.